Marathon [videorecording (DVD)] - Behpoornia, Kimia; Cortez, Tavius; Hansen, Andrew; Roberts, Marc (Actor) (Gravitas Ventures, 2021)
An unprofessional film crew follows five amateur runners as they train for Devil's Canyon Marathon, an offbeat desert race organized by a desperate shoe store owner pulling out all the stops to celebrate its fifteenth year.